Daily field checking list, Walter Rosene, March 4, 1934 - Iowa Ornithologists' Union; Rosene, Walter, 1880-1941 (1934)
Bird checklist dated March 4, 1934. This checklist was used by Walter Rosene to record birds sighted around Beaver Creek with Bob Walker between 7:30 and 10:00.